2004
DOI: 10.1177/1534735404270285
|View full text |Cite
|
Sign up to set email alerts
|

8-oxo-dG Elevated in Children During Leukemia Treatment

Abstract: Changes in oxidative stress in children undergoing chemotherapy for acute lymphoblastic leukemia (ALL) have not been well documented. To determine whether the measurement of the DNA oxidized base 8-oxodeoxyguanosine (8-oxo-dG) may be a useful biomarker in this population, the authors conducted an observational study on 103 children with ALL. Blood samples were collected at diagnosis, during interim maintenance (IM), and during delayed intensification (DI). Blood mononuclear cell 8-oxo-dG, measured with an immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It has been suggested that cancer-induced antioxidant depletion may be associated with increased utilization by the tumor itself or the resulting oxidative stress (23). Chemotherapy per se may also induce oxidative stress and hence increase the utilization of antioxidants (24).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that cancer-induced antioxidant depletion may be associated with increased utilization by the tumor itself or the resulting oxidative stress (23). Chemotherapy per se may also induce oxidative stress and hence increase the utilization of antioxidants (24).…”
Section: Discussionmentioning
confidence: 99%
“…ALL, the most common childhood malignancy, remains the leading cause of cancer-related deaths in children because of treatment resistance cases in which the underlying predisposing factors are poorly understood [31]. The already established variable capacity of ALL patients to process different types of DNA damage after radiotherapy or chemotherapy [31,32], points to the potential role of induction and repair of DNA lesions in the risk or recurrence and overall response to therapy.…”
Section: Introductionmentioning
confidence: 99%
“…An original observational study was submitted by Deborah Kennedy and coauthors working on a project initiated by Kara Kelley at Columbia University on 8-oxodeoxyguanosine (8-oxo-dG) in children receiving treatment for acute lymphoblastic leukemia (ALL). 22 Kennedy and colleagues begin by providing support for the use of 8-oxo-dG as a biomarker for oxidative stress, and they discuss the lack of good data on the effect of diet on the levels of this marker. Current treatment protocols for children with ALL, while effective, generally generate large numbers of oxidative by-products, including ones that can further damage DNA.…”
mentioning
confidence: 99%